2015
DOI: 10.3390/nu7075251
|View full text |Cite
|
Sign up to set email alerts
|

Fruit, Vegetable and Dietary Carotenoid Intakes Explain Variation in Skin-Color in Young Caucasian Women: A Cross-Sectional Study

Abstract: Fruit and vegetables contain carotenoid pigments, which accumulate in human skin, contributing to its yellowness. This effect has a beneficial impact on appearance. The aim was to evaluate associations between diet (fruit, vegetable and dietary carotenoid intakes) and skin color in young women. Ninety-one Caucasian women (Median and Interquartile Range (IQR) age 22.1 (18.1–29.1) years, BMI 22.9 (18.5–31.9) kg/m2) were recruited from the Hunter region (Australia). Fruit, vegetable and dietary carotenoid intakes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Another factor influencing skin coloration is diet. Higher fruit and vegetable intakes are related to a yellower appearance of the skin [35,40]. Women with higher BMI were found to consume less fruits and vegetables [40,41], which, in turn, might result in lower skin yellowness.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor influencing skin coloration is diet. Higher fruit and vegetable intakes are related to a yellower appearance of the skin [35,40]. Women with higher BMI were found to consume less fruits and vegetables [40,41], which, in turn, might result in lower skin yellowness.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has further shown that colour representation [ 24 , 44 , 45 ] and head position [ 25 ] influence the resulting image. Specifically, changes in face colour affect perceived health and attractiveness with higher judgements of redder faces [ 24 , 44 46 ] (but see Burriss et al [ 23 ]), while downward head tilt is perceived as more intimidating through the manipulation of fWHR [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fruit and vegetable consumption is related to the skin yellowness ( b *) axis of the Commission Internationale de l'Eclairage (CIE) L * a * b * colour space, where L * represents skin lightness and positive values of a * and b * represents degrees of redness and yellowness, respectively (Pezdirc et al, ; Stephen, Coetzee, & Perrett, ). Self‐reported increases in fruit and vegetable intake over a 6‐week period have shown to be associated with a measurable increase in skin yellowness ( b *) and redness ( a *) (Whitehead, Re, Xiao, Ozakinci, & Perrett, ).…”
Section: Introductionmentioning
confidence: 99%